Does integrated soil fertility management increase returns to land and labor? Plot-level evidence from Ethiopia - Denise Hörner; Meike Wollni (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
Integrated Soil Fertility Management (ISFM) is widely promoted to enhance soil fertility, yields and livelihoods among smallholders, and ultimately combat environmental degradation. Its core is the combined use of organic and inorganic fertilizers with improved crop varieties. Yet, farmers face adoption barriers, such as additional monetary and labor investments. To date, much of the evidence on ISFM effects comes from experimental field trials instead of micro-level farmer data. In particular, studies on labor outcomes are scarce, but important to assess the viability of ISFM in smallholder settings. This study addresses this gap by providing a comprehensive analysis of ISFM effects on land productivity, net crop value, labor demand, labor productivity and returns to unpaid labor using survey data from over 6,000 teff, maize and wheat plots and 2,000 households in Ethiopia. We employ a multinomial endogenous switching model to account for endogeneity from observed and unobserved heterogeneity. We find that both partial and complete ISFM adoption lead to significant increases in land productivity and net crop value, in particular when improved seeds are used. In moister regions, complementing improved varieties with inorganic fertilizer seems most important, while in drier regions, enhancing it with organic fertilizer appears crucial. ISFM is related to higher labor demand, but also significantly increases labor productivity and financial returns to labor. These findings imply that ISFM can contribute to improve farmers' livelihoods by breaking the nexus between low productivity, environmental degradation and poverty.
Keywords: J23; J24; O13; O33; Q16; 330; Technology adoption; land productivity; labor productivity; crop value; agroecological heterogeneity; multinomial endogenous switching